An Analysis of the Experiential Function in Motivational Dialogue from the Movie “Barbie” (2023): A Discourse Analysis - Pohan, Rizqina Fauziah; Gultom, Qaila Zulhairah; Ajizah, Aulya; Rangkuti, Linda Astuti; Sihite, Meida Rabia (EXCELLENCE: Journal of English and English Education, 2024)
The objective of this study is to investigate whether the motivational dialogue from the movie "Barbie" is successful in terms of experiential function using a discourse analysis approach. The experiential function focuses on Process, Participant, and Circumstance. The movie ‘Barbie’ is chosen because its dialogue motivates and conveys moral lessons to the viewers. This study employs a qualitative research design. Data were collected through observation and documentation. The data were analyzed by employing several steps: separating the dialogue into clauses, analyzing the clauses in terms of experiential function, classifying the elements of experiential function, deriving patterns of experience, and evaluating the success of the dialogue. The analysis revealed there were 32 Processes, with the Verbal Process being the most dominant (40.62%), 37 Participants were identified, with Sayer being the most frequent at (37,14%), and 23 Circumstances, with Extent Circumstance being the most prevalent at (43.47%). Thus, the dialogue effectively motivates and creates an emotional bond with the viewers, fulfilling its intended experiential function. Through detailed analysis, it was revealed that the dialogue's use of Verbal Processes, Participant roles, and Circumstances contributes significantly to its motivational impact and emotional connection with the viewers.